ANALISIS KESULITAN BELAJAR SISWA DALAM MEMAHAMI MATERI GERAK PADA TUMBUHAN DI KELAS VIII SMP - Utomo, Bambang Imam; Ningsih, Kurnia; Tenriawaru, Andi Besse (Universitas Tanjungpura, 2024)
This study aims to determine the percentage of learning difficulties for class VIII students at SMP Negeri 17 Pontianak, approval of learning in the material on movement systems in plants and what factors cause students' learning difficulties on material on movement systems in plants in class VIII SMP Negeri 17 Pontianak. This method uses a case study, with research subjects being class VIII G students. Three instruments were used to collect data, namely diagnostic tests, questionnaires and interviews. The results of the research show that the percentage of indicators regarding the difficulty of class VIII students at SMP Negeri 17 Pontianak in understanding the material on movement in plants is 60% with sufficient criteria. The causal factors that influence students' learning difficulties can be seen from the percentage of internal factors of 63.83 and external factors of 59.93 in the strong and sufficient categories. Thus, class VIII students at SMP Negeri 17 Pontianak experience difficulties caused by internal and external factors.